2009
DOI: 10.1111/j.1600-9657.2008.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of calcium hydroxide and mineral trioxide aggregate on apexification of a replanted tooth: a case report

Abstract: This case report presents the treatment of a right central maxillary incisor of an 8-year old white male patient with history of traumatic avulsion and immediate replantation. The endodontic therapy consisted of periodical changes of calcium hydroxide dressing and a definitive root canal filling with mineral trioxide aggregate (MTA). The treatment was successful without pathologies up to 7 years of follow-up. After the institution of orthodontic treatment a localized and late root resorption was noticed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 9 publications
2
48
0
4
Order By: Relevance
“…27,33 Although we could not find in the scientific literature any report of discolouration in teeth treated with White MTA, in our daily practice we have also observed this phenomenon in primary incisors, canines and molars. In the present investigation, any discolouration that might have occurred did not represent an aesthetic problem as all molars were restored with a stainless steel crown, as recommended by other authors.…”
Section: Discussionmentioning
confidence: 75%
“…27,33 Although we could not find in the scientific literature any report of discolouration in teeth treated with White MTA, in our daily practice we have also observed this phenomenon in primary incisors, canines and molars. In the present investigation, any discolouration that might have occurred did not represent an aesthetic problem as all molars were restored with a stainless steel crown, as recommended by other authors.…”
Section: Discussionmentioning
confidence: 75%
“…Apexification in one or multiple visits has been the most used and predictable type of treatment for avulsed teeth. 18 Pulp revascularization has not been indicated for replanted teeth, in view of the strong possibility of root resorption, requiring long periods of dressing with an alkaline intracanal medication for prevention and stabilization of root resorption. Pulp revascularization therapy was chosen for the present case because of the presence of incomplete root formation and the probability that the use of a medication composed of calcium hydroxide combined with 2% chlorhexidine gel could create an alkaline environment to prevent and stabilize root resorption during a 21-day period.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MTA promotes a mild grey discolouration in the crown after apexifi cation [ 55 ]; it was reported that coronal discolouration was observed in 22.7 % of teeth following white MTA placement in immature open apex teeth [ 68 ]. Severe discolouration after grey MTA pulpotomy in immature permanent teeth was also reported [ 108 ].…”
Section: Drawbacksmentioning
confidence: 95%